COMPARATIVE HISTOLOGICAL STUDY ON THE GLANDS OF SKIN IN BUFFALO AND COW - Ibrahim, Raad Shaalan; Hussein, Amer Muttib (Diyala Agricultural Sciences Journal, 2017)
This study was done to compare between the skin of buffaloes and cows. Six samples from different regions of the body were collected from local abattoirs in Baghdad. The skin specimens were fixed in formalin solution. Routine histological techniques were carried out on these samples. For staining, hematoxylin and eosin stains were used then samples were examined under light microscope. Even the excretory ducts of sweat glands in both cows and buffaloes were stratified cuboidal epithelium, the sweat glands in buffaloes were poorly developed, less numerous, smaller in size and lies deeply in the dermis with longer duct comparing to that of the cows. Their secretory acini were surrounded by fewer number of myoepithelial cells. The apocrine sweat glands were distributed all over the body regions while the merocrine sweat glands were distributed in limited body regions. On the other hand, the sebaceous glands of buffaloes were well developed and appeared as larger in size and more lobulated comparing to the cows. The above thoughts explain why the buffaloes considered as poor thermoregulator animals. In regard to the mechanism of thermoregulation, the present study concluded that there was a reverse relationship between the function of sebaceous and sweat glands.